2017
DOI: 10.1590/1980-57642016dn11-040002
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in cerebral small vessel disease: Update and new concepts

Abstract: ABSTRACT.In recent years, small vessel disease (SVD) has been recognized for its major impact on cognitive impairment in elderly people, where it is often difficult to separate its effects from those of neurodegenerative diseases individually. SVD is a systemic disease, probably related to diffuse endothelial dysfunction, which affects the perforating arterioles, capillaries and venules in the brain. Although often asymptomatic, it is responsible for almost half of all dementia cases and a significant proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…They range from biomarkers implemented on standard clinical scanners which can be used across multiple sites and advanced methods requiring special techniques. Clinically applicable MRI biomarkers include small subcortical infarctions, lacunes of presumed vascular origins, WMHs of presumed vascular origin, perivascular spaces, cerebral microbleeds, and brain atrophy [15,16]. The more advanced MRI biomarkers include blood-brain barrier permeability, magnetic resonance spectroscopy, diffusion MRI (dMRI) cerebral blood flow, cerebral vascular reactivity, and brain connectivity as measured by functional MRI (fMRI) and dMRI [9,11,12].…”
Section: Mri Methods In Vcimentioning
confidence: 99%
See 1 more Smart Citation
“…They range from biomarkers implemented on standard clinical scanners which can be used across multiple sites and advanced methods requiring special techniques. Clinically applicable MRI biomarkers include small subcortical infarctions, lacunes of presumed vascular origins, WMHs of presumed vascular origin, perivascular spaces, cerebral microbleeds, and brain atrophy [15,16]. The more advanced MRI biomarkers include blood-brain barrier permeability, magnetic resonance spectroscopy, diffusion MRI (dMRI) cerebral blood flow, cerebral vascular reactivity, and brain connectivity as measured by functional MRI (fMRI) and dMRI [9,11,12].…”
Section: Mri Methods In Vcimentioning
confidence: 99%
“…In the last ten years the MRI methods used to study cerebral small vessel disease (SVD) have been reviewed by multiple groups [9][10][11][12][13][14][15][16]. The MRI biomarkers used to study SVD are similar to those used for studying other neurodegenerative diseases, such as AD.…”
Section: Diagnosis Of Patients With Chronic Wm Diseasementioning
confidence: 99%
“…Cerebral SVD causes focal lacunar infarction and more diffuse ischemia, referred to as leukoaraiosis [ 83 ]. Although often asymptomatic, it is responsible for almost half of all cases of dementia and for a significant proportion of stroke cases [ 84 ].…”
Section: Impact Of Uremic Toxins On Brain Microcirculationmentioning
confidence: 99%
“…Standards for neuroimaging with a widely accepted terminology permitting comparison of findings between centers have been recommended (STandards for ReportIng Vascular changes on Neuroimaging [STRIVE]) (14). Numerous studies identified MRI markers of SVD (lacunes, white matter hyperintensities, cerebral microbleeds, silent infarcts, white matter changes, global cerebral atrophy, medial-temporal lobe atrophy) as determinants of VaD (18,19). Vascular lesions traditionally attributed to VCI comprise subcortical areas of the brain, especially subfrontal white matter circuits, strategic areas of single infarction such as the dominant thalamus or angular gyrus, deep frontal areas and the left hemisphere, and bilateral brain infarcts or volume-driven cortical-subcortical infarctions reaching a critical threshold of tissue loss or injury (20).…”
Section: Imaging Morphologic Substrates Of Svdmentioning
confidence: 99%